Academic Performance of Undergraduate Students in Stem and Arts Subjects in Bhutan: A Gender Perspective - Tashi Dendup; Sangay Wangmo; Ugyen Yangchen (Universitas Djuanda, 2021)
Academic performance disparities among the gender of students are the cause of concern. Numerous explanations for academic performance disparities, especially in Science Technology Engineering and Mathematics (STEM) and Arts subjects between male and female students, are established in many countries. However, similar studies in Bhutan, especially at the tertiary education level, are scant. Therefore, this study mainly assessed i) students’ perception of STEM and Arts subjects, ii) compared male and female academic performance in STEM and Arts subjects, and iii) studied students' perception of the factors affecting their academic performance. Data were collected from 265 students of four constituent colleges (two Science and Arts colleges each) of the Royal University of Bhutan using semi-structured questionnaires. A multistage sampling (comprising a mixture of purposive and random) was employed. The research used a quantitative approach with descriptive and inferential statistics (Chi-square, t-tests, and binary logistic regressions). The result showed no significant association between students’ gender and their choice of subjects. At Science colleges, female students outperformed male students. In contrast, there were no significant differences in the performance of male and female students at Arts Colleges. Overall, females (71.63 ± 6.35) outperform male (69.57 ± 7.80) students. Hence, there are no stereotypes in STEM and Arts subjects among Bhutanese undergraduate students. However, future research could include parents and lecturers to gather their perspectives on STEM and Arts subjects. Variables, including study hours, communication skills, and Bhutanese Educational Policies, should also be thoroughly investigated as factors affecting students' academic performance